THE EFFECT OF TYPE, CONCENTRATION, AND DURATION OF SUBMERSION IN CHILI SOLUTION TO REDUCE BEEF BACTERIAL CONTAMINATION - Nathania, Pinontoan Kersty Putri; Swacita, Ida Bagus Ngurah; Rudyanto, Mas Djoko (Buletin Veteriner Udayana; Vol. 14 No. 1 February 2022, 2022)
Indonesia has a variety of culinary diversity. One of the basic ingredients commonly used as a culinary is beef. Beef is very susceptible to bacterial contamination. One of the herbs that can be used as an antibacterial is chili. Chili has an active compound that is known as Capsaicin. This research aims to determine the effect of type, concentration and duration of submersion in chili solution into reducing bacterial contamination in meat. This research used Randomized Complete Block Design (RCBD) with 3 x 2 x 3 Factorial Factor, 4 types of chilli pepper (chilli pepper, curly pepper, and large red pepper), 2 chili solution concentration (25% and 50%), and 3 duration of submersion (5, 10, and 15 minutes). Each combination of treatments, the study will be repeated 2 times, so the total number of samples used was 38 samples. The variables that will be measured in this study are bacterial colonies (ALTB) grown on the Nutrient agar media. The results showed that chili solution and duration of submersion has a significant effect (P <0.05) in reducing bacterial contamination in beef while the concentration of chili solution does not have a significant effect (P>0,05).